PESAN MORAL PADA PUISI CERITA BUMI LIMA METER KARYA NAFIAH AL-MA’RAB - Wahyuni, Ulfa; Syafrial, Syafrial; Elmustian, Elmustian (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract : The background of this study was taken by Nafiah Al-Ma'Rab's Five Meter Earth Story poetry on a collection of poems and short stories on History of Smoke by Hening Wicara, Ahmad Ijazi, Bambang Kariyawan Ys, Nafiah Al-Ma’Rab et al. The problem taken is what is the moral message contained in Nafiah Al-Ma’Rab's Five Meter Earth Story poem? This study aims to describe the moral message found in Nafiah Al-Ma’Rab's Five Meter Earth Story poem. The benefits of this study are divided into three types, namely; theoretical, practical and didactic. The method in this study used is qualitative research that describes descriptive data. The data collection technique used is the technique of studying in a book collection of poems and short stories on History of Smoke, and taken from one of the poems entitled Nafiah Al-Ma’Rab's Bumi Lima Meter Story. The data source in this study was taken from a book collection of poems and short stories on History of Smoke. The overall data that the authors found in this study were 23 data, the data were classified into three categories namely; (1) the author's moral message to himself, (2) the author's moral message to other humans, and (3) the author's moral message to his God. The data is; (1) the author's moral message to himself as much as 6 data, (2) the author's moral message to other humans as much as 12 data, and (3) the author's moral message to God as much as 5 data.Key Words: Moral Message, Five Meter Earth Story Poetry.